Capabilities and Requirements of the Elderly Remote Health Monitoring - Ahmad Reza Shamsabadi; Ahmad Delbari; Ameneh Safari; Fatemeh Bahador; Esmaeil Mehraeen (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: Telehealth management systems for elderly people should have the features, capabilities, and infrastructure that meet home care managementchr('39')s diverse needs. Since there is no valid and reliable questionnaire to determine these requirements, this studychr('39')s primary purpose was to determine a telehealth monitoring systemchr('39')s requirements for the elderly and present it as a valid and reliable questionnaire. Methods & Materials: This study was descriptive-analytical and performed in 2019. The items for the  Questionnaire were obtained from a systematic review study. To review, the selected keywords such as elderly, home care, telecare, telehealth, and information technology from 2013 to October 2019 were searched on selected databases. Results: Based on the studychr('39')s findings, the parameters, and requirements of a telehealth monitoring system for the elderly were identified in 97 items. Furthermore, the first 31 items of the questionnaire were removed due to low validity and reliability. In the next phase, the final questionnaire with 66 items, content validity ratio of 99%, Cronbachchr('39')s alpha coefficient (0.9) and desirable correlation coefficient (r=0.85, p<0.05) were designed. Conclusion: In this study, the requirements of a telehealth monitoring system for the elderly were determined, and a valid and reliable questionnaire was developed using these requirements. The questionnaire was designed in five parts: applications, functional requirements, non-functional requirements, tools, and communication infrastructure. Health care system designers may use the study results to determine the applications and requirements of elderly health monitoring systems.